UPAYA PENGEMBANGAN POPULASI TERNAK BABI MELALUI TEKNIK INSEMINASI BUATAN DIPROVINSI SULAWESI UTARA - Mandey, Freelce J; Paputungan, U; Pudjihastuti, E (ZOOTEC, 2018)
ABSTRACTEXPEDIENCY OF INCREASING PIG POPULATION BY ARTIFICIAL INSEMINATION TECHNIQUE IN NORTH SULAWESI PROVINCE.The objective of this study was to evaluate dominant factors affecting pig population breeding by artificial insemination (AI) in North Sulawesi province. Semen of boar (Landrace, Yorkshire and Duroc breeds) were usedto mate the same breeds using AI.Data of 345 piglets from 33 sows were involved in this study. Reproductive data of sows and productivity of piglet form AI were observed at laboratory and field belonging to farmers in Minahasa regency. Pair data of male and female effect were analyzed by t-test for variables.Dominant reproduction factors affecting pig population breeding in North Sulawesi were includingservice per conception, Farrowing rate, AI service efficiency, and Farrowing index.Group of male and superior piglets were higher in productivity that those of female and inferior piglets. Preweaning Average Daily Gain (PW-ADG)groups of inferior (84.85g/h/d)were significantly lower compared with normal (86.59g/h/d), butnot significantly different with PW-ADG of superior birth weight group (85.64 g/h/d).PW-ADG.Thelitter size produced from semen bya boar naturally mated with the same sowsreached the average of 21 piglets per year, while those by a boar mated using AI technique with the same sowsreached the average of 225 piglets per year.Â Keywords:Artificial insemination. Pig reproduction, North Sulawesi provinceÂ